Correlation of Oocyte Morphology with Fertilization Rate and Embryo Quality after Intracytoplasmic Sperm Injection - Suwit Suppinyopong (2018)
To determine whether the morphology of the oocyte assessed under light microscopy is related to the results of intracytoplasmic sperm injection (ICSI). 135 ICSI oocytes from 15 patients were analyzed. Transvaginal ultrasound - guided oocytes retrieval with oocyte morphology evaluation based on shape of the first polar body and perivitelline space followed by ICSI. After 48 hours, embryo quality was evaluated and compared to each pre-injected oocyte morphology. Normal fertilization was achieved in 81.5 per cent of the oocytes (110/135). Abnormal fertilization (3 pronuclei) was 1.5 per cent (2/135). Fertilization rate of oocytes with good morphology was higher than those with poor morphology, but there was no statistical significance (82.4% vs 79.5%; p > 0.05). Oocytes with good morphology were significantly fertilized to be embryos with good quality (p < 0.001). This study suggests that oocyte morphology correlates with embryo quality after ICSI.